2D/2D heterojunction of g–C3N4/SnS2: room-temperature sensing material for ultrasensitive and rapid-recoverable NO2 detection. (23rd July 2020) - Sun, Quan; Hao, Juanyuan; Zheng, Shengliang; Wan, Peng; Li, Jialu; Zhang, Di; Li, Yanqiu; Wang, Tingting; Wang, You
Abstract: Heterojunction engineering plays an indispensable role in improving gas-sensing performance. However, rational heterojunction engineering to achieve room-temperature NO2 sensing with both high response and rapid recovery is still a challenge. Herein, a 2D/2D heterojunction of g–C3 N4 /SnS2 is designed to improve the sensing performance of SnS2 and used for ultrasensitive and rapid-recoverable NO2 detection at room temperature. The pristine SnS2 fails to work at room temperature because of its high resistivity and weak adsorption to NO2 . After combination with g–C3 N4 nanosheets, the g–C3 N4 /SnS2 -based sensor exhibits an extremely high response (503%) and short recovery time (166 s) towards 1 ppm NO2 at room temperature. The improved sensing performance is primarily attributed to the increased adsorption sites and enhanced charge transfer induced by the 2D/2D heterojunctions with large interface contact area. This achievement of g–C3 N4 /SnS2 2D/2D heterostructures demonstrates a promising pathway for the design of sensitive gas-sensing material based on a 2D/2D heterojunction strategy.